2008
DOI: 10.1039/b800720a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the metal-to-ligand ratio on the formation of metal organic complexes

Abstract: Three copper(II) salts with a chloride, bromide or nitrate counterions in combination with the ditopic ligand 1,3-bis(imidazol-1-ylmethyl)benzene (L) were used to study the influence of the metal to ligand molar ratio on the formation of the final product. Single-crystal X-ray analysis revealed structural diversity of the products formed, ranging from discrete species to extended 1D and 2D coordination polymers. Similar types of 1D chains were formed for all counterions.Scheme 1 1,3-Bis(imidazol-1-ylmethyl)ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…The crystal structure investigation revealed that, in the solid state, the compound exists as a dimer of formula [Cu(L OHex )Br(μ-Br)] 2 , with the Br(1) ions binding two symmetry-related units to each other. To the best of our knowledge, this complex is one of the few mono- or di-nuclear bis-pyrazolyl acetate copper complexes [ 81 , 82 ] with uncoordinated acetate moieties, and also one of the relatively not-so-abundant copper complexes showing µ-bridging bromide ions coupled with two pentacyclic N-based ligands [ 83 , 84 , 85 , 86 , 87 , 88 ], described in the CCDC repository [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure investigation revealed that, in the solid state, the compound exists as a dimer of formula [Cu(L OHex )Br(μ-Br)] 2 , with the Br(1) ions binding two symmetry-related units to each other. To the best of our knowledge, this complex is one of the few mono- or di-nuclear bis-pyrazolyl acetate copper complexes [ 81 , 82 ] with uncoordinated acetate moieties, and also one of the relatively not-so-abundant copper complexes showing µ-bridging bromide ions coupled with two pentacyclic N-based ligands [ 83 , 84 , 85 , 86 , 87 , 88 ], described in the CCDC repository [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the coordination polymers synthesis, the choice of cluster subunits like organic linkers and metal ions is of very important because it leads to a variety of unusual shapes polymeric frameworks with large gaps, and novel properties [7,8]. Besides the construction of the building units, the network architecture can also rely on the choice of the molar ratios of the molecular components, temperature, pH and solvent [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It is aforethought an appealing type of flexible organic ligand for coordination polymers. [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, up until now, it still remains a considerable challenge to achieve controllable preparation conditions to produce crystalline CP materials with desired topological and chemical attributes. The reason for this stems from the complex formation conditions that influence the self-assembly and crystallization process; the applied synthetic approach is influenced simultaneously by numerous parameters, including the structural characteristics of the organic ligands, the coordination geometry of central metal ions, the metal/ligand molar ratio, available counteranions, the solvent system, the pH value of the solution, temperature, pressure, and reaction time [1216]. Importantly, the nature of the organic ligand often influences the topology, the stability, the formation, and the crystallization conditions of the resulting hybrid materials.…”
Section: Introductionmentioning
confidence: 99%